Mr. Keating’s Role as English Teacher as Seen in The Main Character of Dead Poet Society the Movie - Afifulloh, M. (Lire Journal (Journal of Linguistics and Literature), 2017)
Dead Poets Society is a classic movie that explores about English teaching-learning class in Welton Academic. Mr. Keating as the main character is described as unusual English teacher who gives a big influence toward his students’ life. This unusual teaching style absolutely opposites with academic policy. The academic administrator intensively warns Mr. Keating about his teaching style although his student very interested on him. This paper attempts to explore Mr. Keating’s roles as teacher as reflected in Dead Poets Society movie. The paper was qualitative study with American studies approach. American studies is multidisciplinary studies of America. In this multidisciplinary approach, the writer uses sociology, psychology and historical approaches to conduct the result of the research. Sociology and psychology are used to explain the roles of teacher in teaching and historical approach is used to explore all data dealt with American teacher fact in the past. The data was collected by various sources; text book, newspaper, internet and some available printed master. This research reveals that English teachers have roles as facilitator, personal models or demonstrator, and as delegator. As facilitator, teacher controls the class and creates good environments and activities, stimulates new information, provides opportunities for collaborative work, to be problem solving and offers students a multiplicity of authentic learning tasks. As personal models, teachers are free to give an example what student should do in the study as long as deals with the object of the study. As delegator, teachers are free to rule their class with target to build cooperation between the students. Those freedoms are used only to make teaching and learning process well done, although, sometime breaks the academic administrator policy